Antropologi Representasi Sebatas Angan Rindu Fina Af’idatussofa-Upik Lestari - Lestariningsih Lestariningsih; Saptono Hadi; Siti Karomah; Agus Hermawan; Redhitya Wempi Ansori (Jurnal Pendidikan : Riset dan Konseptual, 2022)
Literary work is the result of human thought that is conveyed through the medium of language. In this case, literary works not only contain the author's ideas, but literature is a representative of a created civilization. In this study, literary works are seen based on their relationship to reality, the extent to which literary works reflect those that describe life from social reality. One form of literary work that is the result of the author's expression is poetry. This study objectively describes the imagery of poetry in poetry anthologies, in terms of the attractiveness and uniqueness of poetry.